Outcome of Jejuno-Ileal Atresia Associated with Intraoperative Finding of Volvulus of Small Bowel - Shalini Sinha; Yogesh Kumar Sarin (EL-Med-Pub, 2012)
Aim: To compare the outcome of patients with jeuno-ileal atresia (JIA) associated with the intraoperative finding of volvulus of small bowel (group A) with that of JIA without volvulus (group B). Materials and Methods: It is a retrospective observational study conducted at one of the two units of Pediatric Surgery, in a tertiary care public hospital of India, from January 2001 to December 2010. Hospital records were retrieved and analyzed. During this time period, 65 patients with JIA were operated of which 40 (61.5%) had ileal atresia (IA) and 25 (38.5%) had jejunal atresia (JA). Eleven (16.9%) patients had associated intraoperative finding of volvulus of small bowel (Group A) and were studied and compared with group B- not associated with intraoperative findings of volvulus of small bowel (n=54). The demography, clinical features, operative findings, associated anomalies, anastomotic leakage, and outcome were compared. Results: Group A comprising of 6 boys and 5 girls, had 8 IA and 3 JA; one case each of Type 3b and Type 4 JIA was seen. Associated anomalies included meconium ileus (n=2), Down's syndrome (n=1) and malrotation (n=1). Anastomotic leak rate was 75% for IA and 66.7% for JA. The mortality was 91% in Group A, 100% for IA and 67% for JA. Group B comprising of 37 boys and 17 girls, had 32 IA and 22 JA; 2 cases of Type 4 and 1 case of Type 3b JIA was seen. Associated anomalies were malrotation (n=2), meconium ileus (n=1), exomphalos (n=1), gastroschisis (n=1) and ileal duplication cyst (n=1). The anastomotic leak rate for JA was 8/21 (38.1%) and IA was 3/28 (10.7%); persistent obstruction was seen in 3/21(14.3%) JA and 1/28 (3.6%) IA patients. In group B, overall mortality rate was 8/22 (36.4%) for JA and 9/32 (28%) for IA. The morbidity and mortality was significantly higher in group A when compared to group B. Conclusions: JIA associated with volvulus (without malrotation) is a sinister entity with a dismal outcome in our experience.